Posttraumatic Epilepsy in Operation Enduring Freedom/Operation Iraqi Freedom Veterans. Issue 5 (1st May 2014) - Chen, Leo L. K.; Baca, Christine B.; Choe, Jessica; Chen, James W.; Ayad, Miriam E.; Cheng, Eric M.
ABSTRACT: Penetrating traumatic brain injury (TBI) is a well-established risk factor for post-traumatic epilepsy (PTE). However, many veterans in Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF) who suffer from TBI do so from blast injury, and its consequences are not fully known. Two neurologists performed a chart review to describe patterns of injury and health care among all 16 OEF/OIF veterans at the VA Greater Los Angeles Healthcare System who were assigned an outpatient diagnosis of both epilepsy and TBI in 2008–2009. All Veterans were male, and the mean age was 30 years. Blast exposure was the most common mechanism of TBI (81%). Although all Veterans were assigned a diagnosis code of seizures, the diagnosis of PTE was clinically confirmed in only 3 veterans. On the other hand, the diagnosis of post-traumatic stress disorder was confirmed in 81% of the sample and a diagnosis of nonepileptic seizures was suspected in 44% of the sample. Researchers who study PTE among the OEF/OIF population using administrative data also should perform chart reviews to account for the prevalence of psychogenic nonepileptic seizures.